Evaluation of Financial Recording Procedures and Accounting Recognition at Rezki Husada Dental Clinic Based on SAK EMKM - Wahyuni; Idil Rakhmat Susanto; Fitra Nur; Fintha Rahmakasih; Nur Fidya EP; Novita Ardhana (www.amertainstitute.com, 2026)
: This study aims to evaluate the effectiveness of the financial recording procedures at Rezki Husada Dental Clinic against the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), specifically regarding procedures for recording cash inflows and outflows, transaction documentation, and the recognition of inventory, fixed assets, and revenue. The research employs a qualitative descriptive approach with a case study design. Data were collected through direct observation and documentation at Rezki Husada Dental Clinic, as well as by analyzing daily cash records over one fiscal year (365 days of transactions) and comparing them with SAK EMKM standards. While the clinic consistently records daily income and expenses throughout the year, these records lack supporting physical transaction evidence, such as documented memos or receipts. Inventory management for consumables is not conducted systematically, relying instead on narrative descriptions. Furthermore, the clinic lacks a fixed asset inventory and does not calculate depreciation. Revenue is accounted for entirely on a cash basis, without distinguishing patient receivables. Although the daily cash recording system is consistent, the overall accounting practices do not fully align with SAK EMKM, particularly regarding the reliability of transaction evidence and the recognition of inventory and fixed assets. This study focuses on a single clinic and relies solely on secondary data in the form of cash summaries; the research team did not obtain physical transaction evidence or documentation regarding the clinic's inventory and fixed assets, meaning the evaluation of these two aspects is merely indicative. This study offers practical insights into the application of SAK EMKM (Financial Accounting Standards for Micro, Small, and Medium Entities) within micro-scale healthcare service businesses and serves as a guide for developing more robust accounting Standard Operating Procedures (SOPs) for similar clinics.